A perspective for supply chain management: Building a conceptual framework - Luai E. Jraisat (International Journal of Business Science & Applied Management (IJBSAM), 2011)
Supply chain relationships play a significant role in supply chain management to respond to dynamic export market changes. If the dyadic exporter-producer relationships are still weak, they impede the emergence of a high performance supply chain within an export market. This paper develops a conceptual framework for understanding how exporter-producer relationships include not only the relationship system but also network and transaction systems; and thus introduces a more integrated way of looking at supply chain management based on information sharing as a key process between exporters and producers. To achieve this aim, supply chain relationships are reviewed from the perspectives of relationship marketing theory, network theory and transaction cost theory. Findings from previous research are discussed to provide a better understanding of how these relationships have evolved. A conceptual framework is built by offering a central proposition that specific dimensions of relationships, networks and transactions are the key antecedents of information sharing, which in turn influences export performance in supply chain management.
Keywords: 650; supply chain management; marketing; exporter-producer relationship; information sharing